Exercise responses and adaptations in rowers and spinal cord injury individuals - Hagermann, F.; Jacobs, P.; Backus, D.; Dudley, G. A. (Medicine & Science in Sports & Exercise, 2006)
Elite rowers (ROWERS) and those who have had a spinal cord injury (SCI) are different physically in many realms. Both have physical activity histories that affect their lower-extremity extensor muscles in a dramatically different fashion. ROWERS can sustain a 500-W power output during their 5- to 6-min race. After a complete SCI, a 75-W power output might be achieved during a VO2peak test. Elite SCI wheelchair racers can achieve a higher value that is similar to that of a sedentary able-bodied person. ROWERS can attain a [latin capital V with dot above]O2 max of more than 7.5 L[middle dot]min-1 and can tolerate a blood lactate of 30 mmol[middle dot]L-1. After a complete SCI in which muscles become markedly atrophied, a peak [latin capital V with dot above]O2 of 2 L[middle dot]min-1 and a blood lactate of 10 mmol[middle dot]L-1 might be achieved. ROWERS rely on the 75% slow-twitch fiber composition of their trained thigh muscles to train and race. Such activity modestly increases fiber size and markedly increases mitochondrial content. After a complete SCI, affected muscle fibers markedly atrophy, maintain most of their mitochondrial content, and become fast-twitch. These data suggest remarkable plasticity of physical function to the extreme that a marked increase in energy demanding, rather continuous physical activity can make a muscle more "slow-twitch"; so it will demand less energy when contracted. In contrast, SCI eventually causes muscle to be composed of more fast-twitch fibers. Molecular biologists may explain why fast-twitch fibers, which appear ideal for some athletes because of their high power output, are abundant in muscles that are seldom recruited. Until then, our results indicate that the fiber type composition of muscle in humans is stable unless extreme alterations in physical activity are endured.